2014
DOI: 10.2460/javma.244.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Salmonella enterica serotype Infantis infection in humans linked to dry dog food in the United States and Canada, 2012

Abstract: CASE DESCRIPTION--In April 2012, Salmonella enterica serotype Infantis was detected in an unopened bag of dry dog food collected during routine retail surveillance. PulseNet, a national bacterial subtyping network, identified humans with Salmonella Infantis infection with the same genetic fingerprint as the dog food sample. CLINICAL FINDINGS--An outbreak investigation identified 53 ill humans infected with the outbreak strain during January 1 to July 5, 2012, in 21 states and 2 provinces in Canada; 20 (38%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 18 publications
1
43
0
1
Order By: Relevance
“…The S . Infantis isolate in our study was isolated in the outbreak investigation reported by Imanishi et al in 2014 (7). …”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The S . Infantis isolate in our study was isolated in the outbreak investigation reported by Imanishi et al in 2014 (7). …”
Section: Resultssupporting
confidence: 56%
“…As mentioned before, in some cases the same product caused illness in humans and pets (7, 57). One of the most frequently reported risk factors for developing salmonellosis is the feeding of raw food to dogs (11, 5860).…”
Section: Discussionmentioning
confidence: 75%
“…From 2006 to 2008, an outbreak of Salmonella Schwarzengrund, which included 79 illnesses over 21 states, resulted in the recall of 105 brands of dry pet food and the permanent closure of the manufacturing plant (Behravesh et al, 2010). In 2012, there was an outbreak of human Salmonella enterica serotype Infantis infections related to exposure to dry dog food (CDC, 2012;Imanishi et al, 2014). With the dog and cat population in the United States estimated at 65 million and 78 million animals, respectively, according to the 2002 American Pet Product Manufacturers Association National Pet Survey (Finley et al, 2006), a significant human population is exposed to pet food and treats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when feeding a pet wet food from cans and pouches, immediately cover and refrigerate any of the food that is left in the container and any wet food that the pet did not eat during the meal should be thrown away. Dry pet food (in its original bag) should be stored in a clean plastic container with a lid, and the top of the bag should be folded or closed [7].…”
Section: Minimum Median Maximummentioning
confidence: 99%